Photostability of Perovskite Solar Cells: Challenges and Strategies - Ruohan Liu; Runnan Yu; Zhan’ao Tan (Nanomaterials)
Perovskite solar cells (PSCs) have been regarded as a revolutionary technology in the photovoltaic field, offering a promising pathway for efficient and cost-effective solar energy conversion and demonstrating broad prospects for future green energy technologies. However, critical stability challenges, specifically degradation induced by humidity, light, or heat, severely hinder the commercialization of this technology. Specifically, ultraviolet (UV) radiation in the solar spectrum is a major factor leading to the degradation of perovskite materials. This review focuses on the challenges and strategies for addressing the photostability issues of PSCs. A variety of strategies have been explored, which can be classified as external protection (such as UV-blocking encapsulation technologies) and internal optimization approaches (including precise compositional tuning, the incorporation of functional additives, interface engineering, and improvements to charge transport layers). Finally, this review delves into the key scientific challenges and technological bottlenecks currently faced in addressing the UV stability of PSCs and proposes future directions for solving UV stability issues. It also provides an outlook on the future development prospects of these technologies.